2014
DOI: 10.1589/jpts.26.471
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Taekwondo as Security Martial Arts Training on Anaerobic Threshold, Cardiorespiratory Fitness, and Blood Lactate Recovery

Abstract: [Purpose] This study was conducted to determine the influence of Taekwondo as security martial arts training on anaerobic threshold, cardiorespiratory fitness, and blood lactate recovery. [Subjects and Methods] Fourteen healthy university students were recruited and divided into an exercise group and a control group (n = 7 in each group). The subjects who participated in the experiment were subjected to an exercise loading test in which anaerobic threshold, value of ventilation, oxygen uptake, maximal oxygen u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
5
12
0
Order By: Relevance
“…This capacity may be due to a good aerobic system that is improved in response to a systematic TKD training ( Haddad et al, 2011 ; Kim et al, 2015 ), and it is important to speed recovery between rounds and fights ( Bridge et al, 2014 ). Our data corroborate with the other ones ( Kim et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…This capacity may be due to a good aerobic system that is improved in response to a systematic TKD training ( Haddad et al, 2011 ; Kim et al, 2015 ), and it is important to speed recovery between rounds and fights ( Bridge et al, 2014 ). Our data corroborate with the other ones ( Kim et al, 2014 ).…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that obese people with high CRF can have a relatively lower risk of metabolic disorders than obese people with low CRF. In this context, the decrease in body fat and improvements in VO 2max from the exercise intervention program in this study can be a very important factor in increasing HMW adiponectin 33 ) .…”
Section: Discussionmentioning
confidence: 83%
“…Sports athletes are known to have fast HR recovery after maximum exercise. Reports show a fast decline for 1 and 2 min after maximum exercise while, after 3 min, the decline is slower ( Myers et al, 2002 ; Kim et al, 2014 ). The results of this study showed that the nonsmoker group has a significantly higher HR recovery rate at 1 min and until 3 min compared to the smoker group.…”
Section: Discussionmentioning
confidence: 99%